Iron-based polyanion positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202610957678.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的首要目的在于克服现有铁基聚阴离子正极材料的长循环稳定性不佳的问题,提供一种铁基聚阴离子正极材料
本发明公开了一种铁基聚阴离子正极材料。本发明通过掺杂价态≥3的金属离子A,并调节其掺杂摩尔比,使材料中Fe的价态稳定在+2价,同时满足Na化学计量比守恒和电中性。在此条件下,制得的铁基聚阴离子正极材料具有更加稳定的晶格结构和更少的Fe/Na反位缺陷,从而提高了钠离子的扩散速率和电导率。将该材料应用于钠离子电池中,有效提高其放电容量和长循环稳定性,使其在0.1C、1.7~4.3V条件下,放电容量可达112mAh/g以上;且在1C倍率下经过1000次充放电循环后,容量保持率仍高于90%。
Smart Images

Figure CN123017914A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and more specifically, to an iron-based polyanion cathode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries, with their high energy density and long cycle life, are widely used in smart devices, electric vehicles, and energy storage systems. However, due to the limited lithium resources, it is difficult to meet the ever-increasing application demands. In contrast, sodium-ion batteries have significant cost and sustainability advantages due to the abundance of sodium resources. In sodium-ion batteries, the cathode material is a key factor determining battery performance. Currently, suitable cathode materials for sodium-ion batteries mainly include layered oxides, Prussian-type materials, and polyanionic materials. Among them, polyanionic materials have a high theoretical capacity and a suitable operating voltage, thus becoming one of the important cathode candidate materials. However, this material suffers from low electronic conductivity and high impurity phase content, which leads to poor cycle performance of sodium-ion batteries.
[0003] To address the aforementioned problems, existing technologies primarily employ cation doping for improvement. For example, patent application CN118231609A discloses a polyanion-based sodium battery cathode material, its preparation method, and its applications. The polyanion compound in this polyanion-based sodium battery cathode material has the chemical formula Na₄Fe₂O₃. a M b (PO4)2P2O7, where 1.4 ≤ a < 3, 0.005 < b ≤ 1.7, 2.7 < a + b < 3, and M is a transition metal. This technical solution effectively reduces the impurity phase content in polyanionic materials by doping with transition metals and creating iron defects, while improving their sodium ion migration ability, reversible capacity, and energy density.
[0004] However, as application scenarios continue to evolve, sodium-ion batteries often need to withstand thousands of charge-discharge cycles. Poor long-cycle stability of sodium-ion batteries can easily lead to rapid capacity decay, significantly increasing maintenance costs. Furthermore, the aforementioned technical solutions still require further improvement in long-cycle stability. Therefore, how to further enhance the long-cycle stability of polyanion cathode materials has become an urgent technical problem to be solved. Summary of the Invention
[0005] The primary objective of this invention is to overcome the problem of poor long-cycle stability of existing iron-based polyanion cathode materials and to provide an iron-based polyanion cathode material.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned iron-based polyanionic cathode material.
[0007] Another object of the present invention is to provide the use of the above iron-based polyanionic cathode material in the preparation of sodium-ion batteries.
[0008] Another object of the present invention is to provide a positive electrode sheet, which comprises the above iron-based polyanionic cathode material.
[0009] Another object of the present invention is to provide a sodium-ion battery, which comprises the above positive electrode sheet.
[0010] To achieve the above objects, the present invention is realized through the following technical solutions: An iron-based polyanionic cathode material, wherein the iron-based polyanionic cathode material comprises an active material and a carbon coating layer located on the surface of the active material; the molecular formula of the active material is Na4Fe x A y (PO4)2P2O7, wherein A is selected from La 3 + , Sb 3+ , Al 3+ , Ce 3+ , Sm 3+ , Zr 4+ , Sn 4+ , Nb 5+ , Ta 5+ , W 6+ , Mo 6+ one or more of the group; x≥2.8, 2.8<x+y<3, and 4+2x+ny=10, where n is the valence value of A.
[0011] The inventors have found through research that in the iron-based polyanionic cathode material, the metal ion A with a valence state ≥ 3 is used for doping, and by adjusting the molar ratio relationship of doping, Fe in the material is stably maintained at the +2 valence state, while satisfying the Na stoichiometric ratio and electrical neutrality. Under these conditions, the s, p, and d electrons in the A atom all participate in hybridization with oxygen to form A-O bonds with higher bond energy, which effectively stabilizes the crystal lattice structure, suppresses Fe / Na antisite defects through Coulomb interaction, purifies the crystal lattice structure, and improves the diffusion rate of sodium ions. Applying this iron-based polyanionic cathode material to sodium-ion batteries endows the batteries with high discharge capacity and long cycle stability.
[0012] Preferably, said A is selected from La 3+ , Sb 3+ , Al 3+ , Ce 3+ , Sm 3+ , Zr 4+ , Sn 4+ , Nb 5+ , Ta 5+ , W 6+ , Mo 6+At least two of them.
[0013] Meanwhile, the inventors discovered that doping with multiple metal ions can produce a synergistic effect. By forming multiple AO bonds with higher bond energies, the crystal structure can be stabilized more effectively and Fe / Na antisite defects can be suppressed, thereby further improving the discharge capacity and cycle stability of sodium-ion batteries.
[0014] Preferably, the doping site of A is an Fe site.
[0015] Preferably, A is uniformly distributed in the iron-based polyanionic cathode material.
[0016] In this invention, the distribution of element A in the iron-based polyanionic cathode material can be characterized by energy dispersive spectroscopy (EDS). In EDS, a brighter signal color corresponding to element A indicates a higher content. When the signal color corresponding to element A is generally consistent and there are no obvious black areas, it is considered to be uniformly distributed.
[0017] To achieve uniform distribution of element A in iron-based polyanionic cathode materials, this invention employs ball milling to mix the raw materials evenly, followed by calcination.
[0018] The preparation method of the above-mentioned iron-based polyanion cathode material is also within the scope of protection of this invention, which includes the following steps: ball milling and mixing sodium source, iron source, phosphorus source, A source and carbon source to obtain a mixture, and then calcining the mixture to obtain the iron-based polyanion cathode material.
[0019] Preferably, the A source is one or more of the acetate, nitrate, alkoxide or oxide of element A.
[0020] More preferably, the A source is an alkoxide of element A.
[0021] In this invention, the sodium source can be selected from commonly used sodium sources in the art, such as sodium oxalate, sodium acetate, sodium nitrate, sodium carbonate, sodium dihydrogen phosphate, sodium pyrophosphate, or disodium hydrogen phosphate, or one or more thereof. Preferably, the sodium source is sodium dihydrogen phosphate or sodium nitrate.
[0022] In this invention, the iron source can be selected from commonly used iron sources in the art, such as one or more of ferrous acetate, ferrous oxalate, ferric nitrate, ferric phosphate, or ferric oxide. Preferably, the iron source is ferric nitrate.
[0023] In this invention, the phosphorus source can be a commonly used phosphorus source in the art, such as one or more of sodium pyrophosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, sodium phytate, or iron phosphate. Preferably, the phosphorus source is sodium dihydrogen phosphate.
[0024] In this invention, the carbon source can be selected from commonly used carbon sources in the art, such as one or more of starch, citric acid, glucose, sucrose, polyethylene glycol, or polyvinyl alcohol. Preferably, the carbon source is glucose.
[0025] Preferably, the amount of carbon source added is 5 to 30 wt% of the theoretical mass of the active material.
[0026] In this invention, the "theoretical mass of the active material" is calculated using the following formula: .
[0027] Preferably, the ball milling mixing time is 10-12 hours.
[0028] Preferably, the ball milling mixing speed is 400~600 rpm.
[0029] As is well known to those skilled in the art, during the calcination process of polyanion cathode materials, an oxidation reaction will occur if oxygen is present in the system, thereby destroying the crystal lattice of the polyanion cathode material. Therefore, calcination needs to be carried out under an inert atmosphere. Preferably, the inert atmosphere is an argon atmosphere.
[0030] Preferably, the roasting temperature is 500~580℃ and the roasting time is 5~15h.
[0031] The application of the aforementioned iron-based polyanionic cathode material in the preparation of sodium-ion batteries is also within the scope of protection of this invention.
[0032] The present invention also protects a positive electrode sheet comprising the above-mentioned iron-based polyanionic positive electrode material.
[0033] The present invention also protects a sodium-ion battery comprising the above-described positive electrode.
[0034] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses an iron-based polyanion cathode material. By doping with metal ions (A) with a valence state ≥3 and adjusting the doping molar ratio, the valence state of Fe in the material is stabilized at +2, while simultaneously satisfying the stoichiometry conservation and electroneutrality of Na. Under these conditions, the prepared iron-based polyanion cathode material exhibits a more stable crystal structure and fewer Fe / Na antisite defects, thereby improving the diffusion rate and conductivity of sodium ions. When applied to sodium-ion batteries, this material effectively improves their discharge capacity and long-cycle stability, achieving a discharge capacity of over 112 mAh / g under 0.1C and 1.7–4.3V conditions; and retaining over 90% of its capacity after 1000 charge-discharge cycles at 1C. Attached Figure Description
[0035] Figure 1 The image shows the XRD pattern of the iron-based polyanion cathode material prepared in Example 1 of this invention.
[0036] Figure 2 This is the energy dispersive spectroscopy (EDS) analysis diagram of the iron-based polyanionic cathode material prepared in Example 1 of the present invention.
[0037] Figure 3 The image shows the XRD pattern of the iron-based polyanion cathode material prepared in Comparative Example 1 of this invention.
[0038] Figure 4 This is the energy dispersive spectroscopy (EDS) analysis diagram of the iron-based polyanionic cathode material prepared in Comparative Example 1 of this invention.
[0039] Figure 5 This is the energy dispersive spectroscopy (EDS) analysis diagram of the iron-based polyanionic cathode material prepared in Comparative Example 10 of this invention.
[0040] Figure 6 This is a charge-discharge curve of the iron-based polyanion cathode material prepared in Example 1 of the present invention.
[0041] Figure 7 This is a charge-discharge curve of the iron-based polyanion cathode material prepared in Comparative Example 1 of the present invention.
[0042] Figure 8 This is a rate performance diagram of the iron-based polyanion cathode material prepared in Example 1 of the present invention.
[0043] Figure 9 This is a rate performance diagram of the iron-based polyanion cathode material prepared in Comparative Example 1 of the present invention.
[0044] Figure 10 This is a cycle performance diagram of the iron-based polyanion cathode material prepared in Example 1 of the present invention.
[0045] Figure 11 This is a cycle performance diagram of the iron-based polyanion cathode material prepared in Comparative Example 1 of the present invention. Detailed Implementation
[0046] The present invention will be further described below with reference to embodiments and comparative examples. These embodiments are merely typical descriptions of the present invention, but the present invention is not limited thereto. Unless otherwise specified, the test methods used in the following embodiments and comparative examples are conventional methods, and the raw materials and reagents used are commercially available from conventional commercial sources.
[0047] Example 1 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe.2.9 Ta 0.04 (PO4)2P2O7.
[0048] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.9 Ta 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.9 mol of ferric nitrate and 0.04 mol of tantalum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 125.1 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0049] The iron-based polyanion cathode material prepared in this embodiment was subjected to XRD testing, and the results are as follows: Figure 1 As shown.
[0050] from Figure 1 It can be seen that the iron-based polyanionic cathode material prepared in this embodiment is a pure phase, and Ta 5+ Doping at the Fe site.
[0051] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the results are as follows: Figure 2 As shown.
[0052] from Figure 2 It can be seen that in the iron-based polyanionic cathode material prepared in this embodiment, the Ta element is uniformly distributed.
[0053] Example 2 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.9 Nb 0.04 (PO4)2P2O7.
[0054] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.9 Nb 0.04The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.9 mol of ferric nitrate and 0.04 mol of niobium ethanol and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.4 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0055] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Nb 5+ Doping at the Fe site.
[0056] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanion cathode material prepared in this embodiment, the Nb element exhibits a uniform distribution.
[0057] Example 3 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.88 W 0.04 (PO4)2P2O7.
[0058] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.88 W 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.88 mol of ferric nitrate, and 0.04 mol of tungsten isopropoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.9 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0059] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and W 6+ Doping at the Fe site.
[0060] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanion cathode material prepared in this embodiment, the W element exhibits a uniform distribution.
[0061] Example 4 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.92 Zr 0.04 (PO4)2P2O7.
[0062] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.92 Zr 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.92 mol of ferric nitrate, and 0.04 mol of zirconium isopropoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.6 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0063] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Zr 4+ Doping at the Fe site.
[0064] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanion cathode material prepared in this embodiment, the Zr element exhibits a uniform distribution.
[0065] Example 5 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.94 Al 0.04 (PO4)2P2O7.
[0066] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.94 Al 0.04The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.94 mol of ferric nitrate and 0.04 mol of aluminum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.3 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0067] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Al... 3+ Doping at the Fe site.
[0068] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanionic cathode material prepared in this embodiment, the Al element exhibits a uniform distribution.
[0069] Example 6 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.92 Al 0.02 Ta 0.02 (PO4)2P2O7.
[0070] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.92 Al 0.02 Ta 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.92 mol of ferric nitrate, 0.02 mol of aluminum ethoxide and 0.02 mol of tantalum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.7 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0071] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Al... 3+ and Ta 5+ Doping at the Fe site.
[0072] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanionic cathode material prepared in this embodiment, Al and Ta elements showed a uniform distribution.
[0073] Example 7 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.91 Al 0.01 Ta 0.02 Nb 0.01 (PO4)2P2O7.
[0074] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.91 Al 0.01 Ta 0.02 Nb 0.01 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.91 mol of ferric nitrate, 0.01 mol of aluminum ethoxide, 0.02 mol of tantalum ethoxide, and 0.01 mol of niobium ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.8 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0075] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Al... 3+ Ta 5+ 、Nb 5+ Doping at the Fe site.
[0076] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanion cathode material prepared in this embodiment, Al, Ta, and Nb elements are uniformly distributed.
[0077] Example 8 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.8 Ta 0.08(PO4)2P2O7.
[0078] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.8 Ta 0.08 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.8 mol of ferric nitrate and 0.08 mol of tantalum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 125.5 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0079] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Ta... 5+ Doping at the Fe site.
[0080] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanionic cathode material prepared in this embodiment, the Ta element exhibits a uniform distribution.
[0081] Example 9 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.95 Ta 0.02 (PO4)2P2O7.
[0082] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.95 Ta 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.95 mol of ferric nitrate and 0.02 mol of tantalum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 125.0 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0083] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and Ta... 5+ Doping at the Fe site.
[0084] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanionic cathode material prepared in this embodiment, the Ta element exhibits a uniform distribution.
[0085] Example 10 This embodiment provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na4Fe. 2.94 La 0.04 (PO4)2P2O7.
[0086] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.94 La 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.94 mol of ferric nitrate and 0.04 mol of lanthanum oxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 125.2 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0087] The iron-based polyanion cathode material prepared in this embodiment was characterized by XRD, and the test results were similar to those in Example 1. The iron-based polyanion cathode material prepared in this embodiment is a pure phase, and La... 3+ Doping at the Fe site.
[0088] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this embodiment, and the test results were similar to those in Example 1. In the iron-based polyanionic cathode material prepared in this embodiment, the La element exhibits a uniform distribution.
[0089] Comparative Example 1 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the molecular formula of the active material is Na. 3.7 Fe 2.9 Ta 0.1 (PO4)2P2O7.
[0090] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na 3.7 Fe 2.9 Ta 0.1 To obtain the stoichiometric ratio of (PO4)2P2O7, weigh out 3.7 mol of sodium dihydrogen phosphate, 2.9 mol of ferric nitrate, 0.3 mol of phosphoric acid, and 0.1 mol of tantalum ethoxide and mix them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, add 125.9 g of glucose to the system and then ball mill the mixture at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0091] The iron-based polyanion cathode material prepared in this comparative example was characterized by XRD, and the results are as follows: Figure 3 As shown.
[0092] from Figure 3 It can be seen that the iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0093] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this comparative example, and the results are as follows: Figure 4 As shown.
[0094] from Figure 4 It can be seen that the Ta element is uniformly distributed in the iron-based polyanionic cathode material prepared in this comparative example.
[0095] Comparative Example 2 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.96 Cu 0.04 (PO4)2P2O7.
[0096] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.96 Cu 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.96 mol of ferric nitrate and 0.04 mol of copper oxalate and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.9 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0097] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0098] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, Cu elements showed a uniform distribution.
[0099] Comparative Example 3 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.96 Cu 0.02 (PO4)2P2O7.
[0100] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.96 Cu 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.96 mol of ferric nitrate and 0.02 mol of copper oxalate and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.6 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0101] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0102] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, Cu elements showed a uniform distribution.
[0103] Comparative Example 4 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.96 Mn 0.02(PO4)2P2O7.
[0104] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.96 Mn 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.96 mol of ferric nitrate and 0.02 mol of manganese oxalate and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.6 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0105] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0106] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, the Mn element showed a uniform distribution.
[0107] Comparative Example 5 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.97 V 0.02 (PO4)2P2O7.
[0108] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.97 V 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.97 mol of ferric nitrate, and 0.02 mol of vanadium trioxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.7 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0109] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0110] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, the V element showed a uniform distribution.
[0111] Comparative Example 6 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.96 Cr 0.02 (PO4)2P2O7.
[0112] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.96 Cr 0.02 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.96 mol of ferric nitrate, and 0.02 mol of chromium trioxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.6 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0113] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0114] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, the Cr element showed a uniform distribution.
[0115] Comparative Example 7 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the molecular formula of the active material is Na. 4.04 Fe 2.96 Li 0.04 (PO4)2P2O7.
[0116] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na 4.04 Fe 2.96 Li 0.04 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.96 mol of ferric nitrate, 0.04 mol of sodium nitrate, and 0.04 mol of lithium nitrate and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.5 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0117] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0118] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, the Li element showed a uniform distribution.
[0119] Comparative Example 8 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₄Fe₂O₃. 2.75 Ta 0.1 (PO4)2P2O7.
[0120] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.75 Ta 0.1 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate, 2.75 mol of ferric nitrate and 0.1 mol of tantalum ethoxide and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 125.6 g of glucose was added to the system. The mixture was then ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 550°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0121] The iron-based polyanionic cathode material prepared in this comparative example was characterized by XRD, and the test results were similar to those of Comparative Example 1. The iron-based polyanionic cathode material prepared in this comparative example contains the impurity phase Na2FeP2O7.
[0122] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanion cathode material prepared in this comparative example, and the test results were similar to those of Comparative Example 1. In the iron-based polyanion cathode material prepared in this comparative example, the Ta element exhibits a uniform distribution.
[0123] Comparative Example 9 This comparative example provides an iron-based polyanion cathode material, which comprises an active material and a carbon coating layer on the surface of the active material; the active material has the molecular formula Na₂Fe. 0.97 Al 0.02 P2O7.
[0124] The preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na2Fe 0.97 Al 0.02 To obtain the stoichiometric ratio of P2O7, weigh out 2 mol of disodium dihydrogen pyrophosphate, 0.97 mol of ferric nitrate and 0.02 mol of aluminum ethoxide and mix them. Then, add 55.0 g of glucose to the system according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material. Then, ball mill the mixture at 400 rpm for 10 hours to obtain the mixture. S2. The mixture is calcined at 600°C for 12 hours under an argon atmosphere to obtain the iron-based polyanion cathode material.
[0125] Comparative Example 10 This comparative example provides an iron-based polyanion cathode material, and the preparation method of the iron-based polyanion cathode material includes the following steps: S1. According to Na4Fe 2.91 Al 0.06 The stoichiometric ratio of (PO4)2P2O7 was determined by weighing 4 mol of sodium dihydrogen phosphate and 2.91 mol of ferric nitrate and mixing them. Then, according to the carbon source addition amount being 20 wt% of the theoretical mass of the active material, 124.1 g of glucose was added to the system. Subsequently, the mixture was ball-milled at 400 rpm for 10 hours to obtain the mixture. S2. The mixture was calcined at 550°C for 12 hours under an argon atmosphere to obtain the precursor; S3. The precursor was ball-milled and mixed with 0.06 mol of aluminum ethoxide. After being mixed evenly, the mixture was calcined at 600°C for 6 hours under an argon atmosphere to obtain an iron-based polyanion cathode material.
[0126] Energy dispersive spectroscopy (EDS) analysis was performed on the iron-based polyanionic cathode material prepared in this comparative example. The test results are as follows: Figure 5 As shown.
[0127] from Figure 5 It can be seen that the signal color corresponding to Al element is obviously black in the central region of the material, indicating that in the iron-based polyanion cathode material prepared in this comparative example, Al element is distributed in a gradient, and the content gradually decreases from the outside to the inside.
[0128] Electrochemical performance testing 1. Preparation of button batteries The iron-based polyanionic cathode materials prepared in each embodiment and comparative example were used to prepare cathode sheets, which were then assembled into button batteries with sodium metal sheets, glass fiber separators and electrolytes. The electrolyte was a 1 mol / L NaPF6 PC (propylene carbonate) / EMC solution (ethyl methyl carbonate) containing 4 wt% FEC (fluoroethylene carbonate).
[0129] The method for preparing the positive electrode sheet specifically includes the following steps: 2g of iron-based polyanionic cathode material, 0.25g of binder PVDF, and 0.25g of conductive agent acetylene black were dissolved in 10mL of N-methylpyrrolidone and stirred to form a cathode slurry. The slurry was then coated onto aluminum foil using a coating machine and dried in a vacuum drying oven at 120℃ for 10h to obtain the cathode sheet.
[0130] 2. Charge and discharge test The button batteries prepared above were subjected to charge-discharge tests at room temperature, and the test results are shown in Table 1. The charge-discharge curves of the iron-based polyanion cathode materials prepared in Example 1 and Comparative Example 1 are shown in Table 1. Figure 6 and Figure 7 As shown. The test conditions were: voltage range of 1.7~4.3V, current density of 0.1C (1C is 129mA / g).
[0131] 3. Ratio Performance Test The button cells prepared above were subjected to rate performance tests at room temperature, and their rate performance was evaluated by discharge capacity ratio. The test results are shown in Table 1. The rate performance results of the iron-based polyanion cathode materials prepared in Example 1 and Comparative Example 1 are shown in Table 1. Figure 8 and Figure 9 As shown. The test conditions were: voltage range of 1.7~4.3V, current density of 0.1C (1C is 129mA / g).
[0132] The formula for calculating the discharge capacity ratio is as follows: .
[0133] 4. Cyclic stability test The button cells prepared above were subjected to 1000 charge-discharge cycles at room temperature. Their cycle stability was evaluated by the capacity retention rate after 1000 charge-discharge cycles. The test results are shown in Table 1. The cycle stability test results of the iron-based polyanionic cathode materials prepared in Example 1 and Comparative Example 1 are shown in Table 1. Figure 10 and Figure 11 As shown. The test conditions were: voltage range of 1.7~4.3V, current density of 1C (1C is 129mA / g).
[0134] The formula for calculating the capacity retention rate after 1000 charge-discharge cycles is as follows: .
[0135] Table 1 Electrochemical performance test results of various button batteries
[0136] As shown in Table 1, the sodium-ion battery made from the iron-based polyanion cathode material prepared by this invention has a discharge capacity of over 112 mAh / g under the conditions of 1.7–4.3V and 0.1C. Moreover, after 1000 charge-discharge cycles under 1C conditions, the capacity retention rate is still higher than 90%, demonstrating excellent long-cycle stability.
[0137] Comparing with Comparative Example 1, it can be seen that if an oxidation state higher than Fe is used... 2+ When metal ions are doped, and the doping amount satisfies x+y=3, Na deficiency will occur in order to satisfy the stoichiometric ratio conservation and electroneutrality of sodium, which will destroy the crystal structure and ultimately lead to a significant decrease in the long-cycle stability and discharge capacity of sodium-ion batteries.
[0138] Comparing with Comparative Example 2, it can be seen that if the valence state and Fe are used... 2+ When doping with equal amounts of metal ions, if the doping amount satisfies x+y=3, Fe will remain in the +2 valence state, but it will be unable to form metal-O bonds with higher bond energy, thus failing to stabilize the crystal structure and consequently failing to improve the long-cycle stability of sodium-ion batteries.
[0139] Comparing Comparative Examples 3 and 4, it can be seen that if the valence state and Fe are used... 2+ When equal amounts of metal ions are doped, and the doping amount satisfies x + y < 3, the material will promote the partial release of Fe to maintain the stoichiometry and electroneutrality of sodium. 2+ Price increase forms Fe 3+ This causes instability in the crystal lattice structure, thereby reducing the long-cycle stability of sodium-ion batteries.
[0140] Comparing with Comparative Example 5, we can see that if V is used... 3+for doping. Due to the weak bonding strength of V-O bonds, the lattice structure is prone to instability, thereby reducing the long-cycle stability of sodium-ion batteries.
[0141] As can be seen from the comparison with Comparative Example 6, if a valence state higher than that of Fe 2+ is adopted for doping with metal ions, when the doping amount is insufficient to simultaneously satisfy 2.8<x+y<3 and 4+2x+ny=10, the material will cause part of Fe to maintain the stoichiometric ratio conservation of sodium and electrical neutrality 2+ to increase its valence to form Fe 3+ , resulting in unstable lattice structure, thus reducing the long-cycle stability of sodium-ion batteries.
[0142] As can be seen from the comparison with Comparative Example 7, if a valence state lower than that of Fe 2+ is adopted for doping with metal ions, the long-cycle stability of sodium-ion batteries cannot be effectively improved either.
[0143] As can be seen from the comparison with Comparative Examples 8 to 9, when the anion in the iron-based polyanionic cathode material is P2O7 4- or the stoichiometric number of iron element is less than 2.8, even if a valence state higher than that of Fe 2+ is adopted for doping with metal ions, the long-cycle stability of sodium-ion batteries still cannot be effectively improved.
[0144] As can be seen from the comparison with Comparative Example 10, when the metal ions in the iron-based polyanionic cathode material present a gradient distribution, the lattice structure will be unstable, which in turn leads to a decrease in the long-cycle stability of the sodium-ion battery.
[0145] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various variations or modifications within the scope of the claims, which do not affect the essential content of the present invention.
Claims
1. An iron-based polyanionic cathode material, characterized in that, The iron-based polyanionic positive electrode material comprises an active material and a carbon coating layer located on the surface of the active material; the molecular formula of the active material is Na4Fe x A y (PO4)2P2O7, wherein A is selected from La 3+ , Sb 3+ , Al 3+ , Ce 3+ , Sm 3+ , Zr 4+ , Sn 4+ , Nb 5+ , Ta 5+ , W 6+ , Mo 6+ one or more of the group; x≥2.8, 2.8<x+y<3, and 4+2x+ny=10, where n is the valence value of A.
2. The iron-based polyanionic cathode material according to claim 1, characterized in that, The A is selected from La. 3+ Sb 3+ Al 3+ Ce 3+ 、Sm 3+ Zr 4+ Sn 4+ 、Nb 5+ Ta 5+ W 6+ Mo 6+ At least two of them.
3. The iron-based polyanionic cathode material according to claim 1, characterized in that, The doping site of A is the Fe site.
4. The iron-based polyanionic cathode material according to claim 1, characterized in that, The A is uniformly distributed in the iron-based polyanion cathode material.
5. The method for preparing the iron-based polyanionic cathode material according to any one of claims 1 to 4, characterized in that, The process includes the following steps: ball milling and mixing sodium source, iron source, phosphorus source, A source and carbon source to obtain a mixture, and then calcining the mixture to obtain the iron-based polyanion cathode material.
6. The preparation method according to claim 5, characterized in that, The amount of carbon source added is 5-30 wt% of the theoretical mass of the active material.
7. The preparation method according to claim 5, characterized in that, The roasting temperature is 500~580℃, and the roasting time is 5~15h.
8. The application of the iron-based polyanionic cathode material according to any one of claims 1 to 4 in the preparation of sodium-ion batteries.
9. A positive electrode plate, characterized in that, The positive electrode comprises the iron-based polyanionic positive electrode material according to any one of claims 1 to 4.
10. A sodium-ion battery, characterized in that, The sodium-ion battery comprises the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Polyanion-based sodium battery positive electrode material as well as preparation method and application thereof
CN118231609A
